Development of halal nutrition framework - Abdul Latif, Mariam; Ab Rahman, Suhaimi (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
The preservation of future generation and the protection of consumer welfare, as contained in the “Maqasid Shariah”, is a priority in view of the incremental negative behaviours existing in today’s societies at large. This qualitative research on halal nutrition focused on halal food consumed by the Prophet Muhammad SAW and his eating practices which will affect any individual in the areas of mind, spirit, intellect, physiology and health. Some foods mentioned in the Quran and Hadith were studied to associate the relationship of halal food, human development and health. The research attempted to develop the framework of Halal Nutrition to provide proper nutrition guidelines for quality and better consumption of halal food for the future generation.